2013
DOI: 10.4254/wjh.v5.i8.445
|View full text |Cite
|
Sign up to set email alerts
|

Serum complement C4a and its relation to liver fibrosis in children with chronic hepatitis C

Abstract: Serum complement C4a did not correlate with any of transaminases, HCV viremia or with the histopathological scores. Although C4a decreased with higher stages of fibrosis, this change was not significant enough to predict individual stages of fibrosis. Yet, it could predict significant fibrosis with acceptable clinical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a proteomic survey of serum samples from HCV-infected patients, liver fibrosis stage was associated with a decrease in C3, C4, and Factor H-related protein-1, a regulatory C3b-binding protein ( 24 ). C4a, a cleavage product of C4 that contrasts with C3a and C5a with regard to biologic function, was reported to be negatively correlated with the stage of liver fibrosis in children with chronic HCV infection, serum levels being significantly lower in HCV children with advanced fibrosis than those with no/mild fibrosis ( 25 ); the significance of this study, however, was limited by the low numbers of HCV-infected children, and the fact that C4a may increase as a function of classical pathway activation and C4 consumption. In a murine genomic study, the gene encoding C5 was identified as a quantitative trait locus associated with the development of liver fibrosis ( 26 ).…”
Section: Fibrosis and Regenerationmentioning
confidence: 99%
“…In a proteomic survey of serum samples from HCV-infected patients, liver fibrosis stage was associated with a decrease in C3, C4, and Factor H-related protein-1, a regulatory C3b-binding protein ( 24 ). C4a, a cleavage product of C4 that contrasts with C3a and C5a with regard to biologic function, was reported to be negatively correlated with the stage of liver fibrosis in children with chronic HCV infection, serum levels being significantly lower in HCV children with advanced fibrosis than those with no/mild fibrosis ( 25 ); the significance of this study, however, was limited by the low numbers of HCV-infected children, and the fact that C4a may increase as a function of classical pathway activation and C4 consumption. In a murine genomic study, the gene encoding C5 was identified as a quantitative trait locus associated with the development of liver fibrosis ( 26 ).…”
Section: Fibrosis and Regenerationmentioning
confidence: 99%
“…Commonly downregulated complement proteins are important mediators of inflammation and contribute to the regulation of the immune response. C4, a predisposing factor to autoimmune chronic active hepatitis [69], is expressed lowly in chronic hepatitis C patient compared to that in controls [70]. Low serum levels of complement in viral hepatitis are associated with high titers of hepatitis-associated antigen [71].…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47] Other studies further revealed that serum concentrations of C3, C4a, and C5a had a negative relationship with liver fibrosis stages and the Child-Pugh score. [48][49][50] These studies show that the levels of complement components may be an indicator of liver fibrosis or cirrhosis stage. 51 There are two possible mechanisms: the reduction of complement synthesis after severe liver injury and excessive complement depletion.…”
Section: The Complement System Participates In Alcoholic Hepatic Fibrmentioning
confidence: 99%